Supplementation of Threonine and Tryptophan in Feed with Different Crude Protein Levels on Body Dimensions of Native Chickens in the Grower Phase (6 - 14 Weeks) - Ori Onesimus Maunaben; Charles V Lisnahan; Gerson F Bira (Journal of Tropical Animal Science and Technology, 2022)
The purpose of this study is to find out the influence of feeding different levels of protein in feed on the dimensions of the body of the village chicken grower phase (6-14 weeks), to find out the addition of amino acids treonine and tryptophan in feed to the dimensions of the body of the village chicken grower phase (6-14 weeks) and to know the interaction of protein leveling and the addition of amino acids treonine and tryptophan in feed to the dimensions of the body of the village chicken grower phase (6-14 weeks). This research has been conducted in Sasi Subdistrict, Kefamenanu City District, North Central Timor Regency for 8 weeks from October-December 2020. This study used 6 weeks old native chickens as many as 120 heads. The method used in this study is a complete random design of factorial patterns of 2 x 3 i.e. 2 levels of amino acids and 3 levels of coarse protein. Treatment given A1C1 (treonine 0.50% + tryptophan 0.15% + protein 15%), A1C2 (treonine 0.50% + tryptophan 0.15% + protein 17%), A1C3 (treonine 0.50% + tryptophan 0.15% + protein 19%), A2C1 (treonine 0.75% + tryptophan 0.20% + protein 15%), A2C2 (treonine 0.75% + tryptophan 0.20% + protein 17%), A2C3 (treonine 0.75% + tryptophan 0.20% + protein 19%). The variables observed in this study were weight, chest circumference, body length, length of sternum, femur length, tibia length, shank length, shank circumference and finger length. The data obtained was analyzed using variance analysis and multiple distance tests. Statistical analysis showed that crude protein levels had an unreal effect on chest circumference, body length, breastbone length, femur length, tibia length, shank length, shank circumference and finger length. Levels of amino acids (treonine + tryptophan) have a noticeable effect on weight, chest circumference, body length, length of sternum, tibia length, shank length and finger length. There is an interaction between amino acids (treonine + tryptophan) and crude protein levels against chest circumference, femur length, shank circumference and finger length.